2021
DOI: 10.1108/ijm-03-2021-0167
|View full text |Cite
|
Sign up to set email alerts
|

Analysing workforce development challenges in the Industry 4.0

Abstract: PurposeThe aim of this paper is to identify and analyse workforce development challenges in the digital age by first, presenting these challenges and relationship between them, and then proposing a structural model that categorizes these challenges and proposes suggestions for managers to improve human resources practices and firm performance.Design/methodology/approachFuzzy total interpretive structural modelling (TISM) is used as the methodology, which gives an interpretive structural model by presenting dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…Information and Communication Technology as a support for thinking is a learning objective in any school curriculum. In the same vein, analytical thinking and interdisciplinary thinking, which help solve problems, are yet other concerns of educators in the Industry 4.0 (Ozkan-Ozen & Kazancoglu, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Information and Communication Technology as a support for thinking is a learning objective in any school curriculum. In the same vein, analytical thinking and interdisciplinary thinking, which help solve problems, are yet other concerns of educators in the Industry 4.0 (Ozkan-Ozen & Kazancoglu, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Behavioral competencies play a vital role in supporting these workers in understanding the business environment, finding creative solutions, promoting collaboration among their team members and also becoming aware of internal and external stakeholders' needs (Costa and Santos, 2017;De Mauro et al, 2019;Mitchell et al, 2021;Shirani, 2016;Verma et al, 2019). Indeed, research (Beck and Libert, 2017;Capgemini, 2019;Ozkan-Ozen and Kazancoglu, 2021;Singh et al, 2021) has claimed that behavioral/emotional intelligence competencies are expected to grow in importance over the next few years and become a differentiator in the digital era in which artificial intelligence and machine learning will progressively automate routine tasks. However, in the past decade, the literature has highlighted the relevance of behavioral competencies for enabling data analysts and scientists to achieve an outstanding performance, and these studies are primarily based on anecdotal evidence or analyses of Web-based job postings and LinkedIn profiles (De Mauro et al, 2019;Ecleo and Galido, 2017;Verma et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…, 2019). Indeed, research (Beck and Libert, 2017; Capgemini, 2019; Ozkan-Ozen and Kazancoglu, 2021; Singh et al. , 2021) has claimed that behavioral/emotional intelligence competencies are expected to grow in importance over the next few years and become a differentiator in the digital era in which artificial intelligence and machine learning will progressively automate routine tasks.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the research, and organization-level maturity model was developed to optimize overall sociotechnical work system performance in the context of rapid technological development in manufacturing industries (Reiman et al, 2021). Study results showed that lack of IT/digital skills has a critical role in workforce development for Industry 4.0 (Ozen and Kazancoglu, 2021).…”
Section: Key (Industry 4 or I4 Or I40 Or Industry 40) And ( Protection Or Safety Or Security Or Resilience Or Vulnerability)mentioning
confidence: 99%